What contraception do women use after experiencing complications from abortion? an analysis of cohort records of 18,688 postabortion care clients in Tanzania - Colin Baynes; J. Kahwa; G. Lusiola; F. Mwanga; J. Bantambya; L. Ngosso; M. Hiza (BMC, 2019)
Abstract Background The family planning component of postabortion care (PAC) is critical, as it helps women to prevent unintended pregnancies and reduce future incidence of life-threatening unsafe abortion. In Tanzania, PAC was recently decentralized from tertiary-level district hospitals to primary health care dispensaries in four regions of the country. This analysis describes interventions used to improve access to high quality PAC services during decentralization; examines results and factors that contribute to PAC clients' voluntary uptake of contraception; and develops recommendations for improving postabortion contraceptive services. Methods This analysis uses service delivery statistics of 18,688 PAC clients compiled from 120 facilities in Tanzania between 2005 and 2014. Results This study suggests that efforts to integrate postabortion family planning into treatment for incomplete abortion contributed to higher postabortion contraceptive uptake (86%). Results indicate that variables associated with significant differences in contraceptive uptake were facility level, age, gestational age at the time of treatment, and uterine evacuation technology used. Conclusion The experience of expanding PAC services in Tanzania suggests that integrating contraceptive services with treatment for abortion complications can increase family planning use.